2006
DOI: 10.1002/app.23100
|View full text |Cite
|
Sign up to set email alerts
|

CO2‐facilitated transport through poly(N‐vinyl‐γ‐sodium aminobutyrate‐co‐sodium acrylate)/polysulfone composite membranes

Abstract: Poly(N-vinyl-␥-sodium aminobutyrate-cosodium acrylate) (VSA-SA)/polysulfone (PS) composite membranes were prepared for the separation of CO 2 . VSA-SA contained secondary amines and carboxylate ions that could act as carriers for CO 2 . At 20°C and 1.06 atm of feed pressure, a VSA-SA/PS composite membrane displayed a pure CO 2 permeation rate of 6.12 ϫ 10 Ϫ6 cm 3 (STP)/cm 2 s cmHg and a CO 2 /CH 4 ideal selectivity of 524.5. In experiments with a mixed gas of 50 vol % CO 2 and 50 vol % CH 4 , at 20°C and 1.04 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…3 [49,51,52,[58][59][60][61][62][63][64][65] summarizes the results of various FSC membranes having different carriers. It can be seen that only a few membranes obtained high selectivity along with reasonably high CO 2 permeance values.…”
Section: Fixed-site-carrier (Fsc) Membranesmentioning
confidence: 99%
“…3 [49,51,52,[58][59][60][61][62][63][64][65] summarizes the results of various FSC membranes having different carriers. It can be seen that only a few membranes obtained high selectivity along with reasonably high CO 2 permeance values.…”
Section: Fixed-site-carrier (Fsc) Membranesmentioning
confidence: 99%
“…Wang et al reported an excellent CO 2 /CH 4 selectivity through poly(Nvinyl-γ-sodium aminobutyrate-co-sodium-acrylate) (VSA-SA)/PSf composite membrane [75]. VSA-SA has a secondary amine and a carboxylate ion, which can reversibly react with CO 2 and thus can be expected to act as carriers for CO 2 .…”
Section: Facilitated Transport Membranesmentioning
confidence: 99%
“…For example, presence of amide/amine functionality enhanced permeation properties of acid gas CO 2 in poly(N-vinyl-␥-sodium aminobutyrate) [14] and polysulfone [15] than respective polymer without such functionality. This notion is not limited only to polymers, as aqueous solutions of alkanolamines are being used industrially as absorbents for acidic gases such as CO 2 and H 2 S since 1930 [15].…”
Section: Introductionmentioning
confidence: 98%